The Legacy of Hurricanes, Historic Land Cover, and Municipal Ordinances on Urban Tree Canopy in Florida (United States) - Salisbury, Allyson B.; Koeser, Andrew K.; Hauer, Richard J.; Hilbert, Deborah R.; Abd-Elrahman, Amr H.; Andreu, Michael G.; Britt, Katie; Landry, Shawn M.; Lusk, Mary G.; Miesbauer, Jason W.; Thorn, Hunter (Frontiers in Forests and Global Change, 2022)
Urban Tree Canopy (UTC) greatly enhances the livability of cities by reducing urban heat buildup, mitigating stormwater runoff, and filtering airborne particulates, among other ecological services. These benefits, combined with the relative ease of measuring tree cover from aerial imagery, have led many cities to adopt management strategies based on UTC goals. In this study, we conducted canopy analyses for 300 cities in Florida to assess the impacts of development practices, urban forest ordinances, and hurricanes on tree cover. Within the cities sampled, UTC ranged from 5.9 to 68.7% with a median canopy coverage of 32.3% Our results indicate that the peak gust speeds recorded during past hurricanes events were a significant predictor of canopy coverage (P = 0.001) across the sampled cities. As peak gust speeds increased from 152 km/h (i.e., a lower-intensity Category 1 storm) to 225 km/h (lower-intensity Category 4 and the maximum gusts captured in our data), predicted canopy in developed urban areas decreased by 7.7%. Beyond the impacts of hurricanes and tropical storms, we found that historic landcover and two out of eight urban forest ordinances were significant predictors of existing canopy coverage (P-landcover < 0.001; P-tree preservation ordinance = 0.02, P-heritage tree ordinance = 0.03). Results indicate that some local policies and tree protections can potentially impact urban tree canopy, even in the face of rapid development and periodic natural disturbances.